Understanding Why Consumers Don't Skip Pre-Roll Video Ads. Issue 3 (3rd July 2017) - Campbell, Colin; Mattison Thompson, Frauke; Grimm, Pamela E.; Robson, Karen
Abstract : Pre-roll advertising is a novel form of online video advertising that provides consumers with an option to skip after viewing a brief forced segment. Pre-roll ads are unique from other forms of online advertising because pre-roll ads play in exactly the space in which consumers are expecting to view their intended content. Such interruption and obstruction not only heightens consumer irritation but also causes attention-getting tactics, which are redundant in a highly attentive state, to backfire. For these reasons, existing ad avoidance literature may not adequately address this unique format. Employing a large industry data set of pre-roll ads representing multiple countries and product categories, we empirically examine skipping behavior using a broader range of ad characteristics than previous research. We propose that less complex affective ad characteristics increase skipping by failing to engage cognitive resources and therefore leaving cognitive resources available to experience irritation. We further posit that, in a pre-roll context, attention-getting ad characteristics are not only superfluous but actually increase the likelihood consumers recognize pre-roll content as advertising and skip. Our empirical findings support these assertions, identifying new factors driving ad avoidance, and calling into question the applicability of attention-getting advertising approaches in the novel pre-roll environment.